EVALUASI TEPAT PASIEN, TEPAT OBAT DAN TEPAT DOSIS ANTIPSIKOTIK PASIEN RAWAT INAP SKIZOFRENIA PARANOID DI RSJ SAMBANG LIHUM - Alexxander, Alexxander; Pratiwi, Restu Dwi (Jurnal Insan Farmasi Indonesia, 2024)
Schizophrenia is a severe brain disorder which is a combination of hallucinations, delusions, disordered thinking and behavioral disturbances. Paranoid schizophrenia is known to be the most common type in Sambang Lihum Hospital in 2023. The main therapy for the treatment at schizophrenia is antipsychotics with a strong effect, which treat behavioral disorders, including psychosis. Improvement of symptoms seen from the PANSS-EC which is an assessment instrument in patients with severe mental disorders/schizophrenia, so that rationality is very important to consider the principle of clinical use benefits. This study aims to determine the percentage pattern of use and rationality of antipsychotics on the successful outcomes of paranoid schizophrenia patients at Sambang Lihum Sambang Hospital, South Kalimantan in 2023.The results of the study showed that the most common drug use patterns in the typical-atypical combination category were haloperidol and clozapine, and the rationality for accuracy was 100% correct dose, 100% correct drug and 99.1% correct patient, with the outcome of successful PANSS-EC discharge of ≤ 15 was 100%.